Analiza skuteczności terapeutycznej metody MDT McKenzie zastosowanej w leczeniu zespołu zaburzeń strukturalnych w odcinku szyjnym kręgosłupa u 26-letniego mężczyzny – opis przypadku = Analysis of therapeutic efficacy of MDT McKenzie method used in the treatment of cervical spine structural disorders in a 26-year-old man - a case report - Porzych, Piotr; Pyskir, Małgorzata; Ratuszek-Sadowska, Dorota; Dzierżanowski, Maciej; Trela, Ewa; Nowacka, Krystyna; Hagner-Derengowska, Magdalena (Journal of Education, Health and Sport, 2016)
Porzych Piotr, Pyskir Małgorzata, Ratuszek-Sadowska Dorota, Dzierżanowski Maciej, Trela Ewa, Nowacka Krystyna, Hagner‑Derengowska Magdalena. Analiza skuteczności terapeutycznej metody MDT McKenzie zastosowanej w leczeniu zespołu zaburzeń strukturalnych w odcinku szyjnym kręgosłupa u 26-letniego mężczyzny – opis przypadku = Analysis of therapeutic efficacy of MDT McKenzie method used in the treatment of cervical spine structural disorders in a 26-year-old man - a case report. Journal of Education, Health and Sport. 2016;6(6):491-504. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.56367 http://ojs.ukw.edu.pl/index.php/johs/article/view/3637 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 05.05.2016. Revised 25.05.2016. Accepted: 16.06.2016. Analiza skuteczności terapeutycznej metody MDT McKenzie zastosowanej w leczeniu zespołu zaburzeń strukturalnych w odcinku szyjnym kręgosłupa u 26-letniego mężczyzny – opis przypadku Analysis of therapeutic efficacy of MDT McKenzie method used in the treatment of cervical spine structural disorders in a 26-year-old man - a case report Piotr Porzych1, Małgorzata Pyskir1, Dorota Ratuszek-Sadowska1, Maciej Dzierżanowski2, Ewa Trela1, Krystyna Nowacka1, Magdalena Hagner‑Derengowska3,4 1. Katedra i Klinika Rehabilitacji, Collegium Medicum im. Ludwika Rydygiera w Bydgoszczy, Uniwersytet Mikołaja Kopernika w Toruniu 2. Katedra Fizjoterapii, Zakład Terapii Manualnej, Collegium Medicum im. Ludwika Rydygiera w Bydgoszczy, Uniwersytet Mikołaja Kopernika w Toruniu 3. Bydgoska Szkoła Wyższa w Bydgoszczy 4. Katedra Neuropsychologii Klinicznej, Collegium Medicum im. Ludwika Rydygiera w Bydgoszczy, Uniwersytet Mikołaja Kopernika w Toruniu Streszczenie Bóle występujące w obrębie szyi są zjawiskiem powszechnym. Wielogodzinne, wymuszone pozycje statyczne związane z pracą zawodową czy procesem edukacyjnym doprowadzają do przeciążeń kręgosłupa. Konsekwencją przeciążeń są zaburzenia funkcji kręgosłupa oraz zmiany strukturalne tkanek występujących w jego okolicy. Zmianom tym często towarzyszy ból. Złożona biomechanika kręgosłupa oraz różnorodność tkanek funkcjonalnie z nim związanych, stanowi istotny problem diagnostyczny. Metoda McKenzie poprzez opracowany model badania oparty na wywiadzie i badaniu przedmiotowym, pozwala wyodrębnić pacjentów o jednorodnym zaburzeniu narządu ruchu. Na jego podstawie zdiagnozować można mechaniczne źródło pochodzenia objawów oraz określić strukturę, która je generuje. W pracy opisano przypadek 26-letniego mężczyzny z bólem karku i kręczem prawostronnym, który został poddany terapii mechanicznej, poprzedzonej diagnozowaniem mechanicznym, w wyniku którego stwierdzono wystąpienie zespołu zaburzeń strukturalnych. Słowa kluczowe: kręcz karku, terapia mechaniczna, MCS Zebris. Abstract Pain occurring in the neck are common phenomenon. Forced, static and lasting many hours positions associated with work or educational process lead to overloading of the spine. Disorders of the spine function and structural changes of adjoining issue are the consequence of overloading. These changes are often associated by pain. The highly complicated spine biomechanics and a variety of functionally related tissues are an important diagnostic problem. McKenzie method allows to specify patients with homogeneous musculoskeletal disorder through elaborated diagnostic procedure based on an interview and physical examination. Mechanical cause of symptoms and structure that generates it can be identify based on it. This paper describes the case of 26-year-old man with neck pain and right torticollis, which has been submited to a mechanical treatment, preceded by a mechanical diagnosis, which concluded the complex of structural disorders. Key words: torticollis, mechanical treatment, MCS Zebris.